2018
DOI: 10.3389/fnmol.2018.00001
|View full text |Cite
|
Sign up to set email alerts
|

Kv2 Ion Channels Determine the Expression and Localization of the Associated AMIGO-1 Cell Adhesion Molecule in Adult Brain Neurons

Abstract: Voltage-gated K+ (Kv) channels play important roles in regulating neuronal excitability. Kv channels comprise four principal α subunits, and transmembrane and/or cytoplasmic auxiliary subunits that modify diverse aspects of channel function. AMIGO-1, which mediates homophilic cell adhesion underlying neurite outgrowth and fasciculation during development, has recently been shown to be an auxiliary subunit of adult brain Kv2.1-containing Kv channels. We show that AMIGO-1 is extensively colocalized with both Kv2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
165
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(174 citation statements)
references
References 59 publications
7
165
2
Order By: Relevance
“…Immunoblotting for AMIGO-1 whole brain expression revealed ≈25% lower expression in Kcnb1 R/+ and ≈50% lower expression in Kcnb1 R/R mice compared to WT littermates ( Figure 3F,G). The observed reduction of AMIGO-1 in Kcnb1 G379R mice is in contrast to our previous studies of brain sections from Kcnb1 +/and Kcnb1 -/mice (Bishop et al, 2018), in which AMIGO-1 immunolabeling was only lost in neurons that typically express high levels of KV2.1 relative to KV2.2, but was expressed normally in neurons that express KV2.2, such as CA1 pyramidal neurons ( Figure 3A).…”
Section: Lower K V 21 Channel Expression In Kcnb1 G379r Micecontrasting
confidence: 99%
See 3 more Smart Citations
“…Immunoblotting for AMIGO-1 whole brain expression revealed ≈25% lower expression in Kcnb1 R/+ and ≈50% lower expression in Kcnb1 R/R mice compared to WT littermates ( Figure 3F,G). The observed reduction of AMIGO-1 in Kcnb1 G379R mice is in contrast to our previous studies of brain sections from Kcnb1 +/and Kcnb1 -/mice (Bishop et al, 2018), in which AMIGO-1 immunolabeling was only lost in neurons that typically express high levels of KV2.1 relative to KV2.2, but was expressed normally in neurons that express KV2.2, such as CA1 pyramidal neurons ( Figure 3A).…”
Section: Lower K V 21 Channel Expression In Kcnb1 G379r Micecontrasting
confidence: 99%
“…Immunohistochemistry and immunoblotting experiments revealed that both KV2.2 and AMIGO-1 immunoreactivity was substantially lower in sections and whole brain membrane preparations from Kcnb1 R/R mice. KV2.1 and KV2.2 form heteromeric channels, with most complexes containing AMIGO-1 auxiliary subunits (Bishop et al, 2018;Kihira et al, 2010;Peltola et al, 2011a). We hypothesize that the lower KV2.2 and AMIGO-1 immunoreactivity is due to their altered subcellular localization, as both proteins were diffusely distributed throughout the ER rather than clustered at the PM (for a full discussion see (Bishop et al, 2018)).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…How Kv2 ion channels influence neuronal excitability is of particular interest because accumulating evidence demonstrates these exceptionally dynamic channels are targets of a remarkable range of influences that can alter their functions (Murakoshi et al 1997;Misonou et al 2004Misonou et al , 2005O'Connell et al 2006O'Connell et al , 2010Redman et al 2007;Mohapatra et al 2009;Plant et al 2011;Steinert et al 2011;Fox et al 2013). In some cultured neurons, high-density clusters of Kv2 channels are largely low or non-conducting, and it is possible that the channel proteins have additional 'non-conducting' functions (O'Connell et al 2010;Fox et al 2013;Bishop et al 2018;Kirmiz et al 2018). However, the data presented here, together with other reports (Du et al 2000;Malin & Nerbonne, 2002;Guan et al 2007Guan et al , 2013Johnston et al 2008;Mohapatra et al 2009;Liu & Bean, 2014), suggest that the electrical function of Kv2 channels in native neuronal membranes is substantial and strongly contributes to neural function.…”
Section: Physiological Role Of Kv2 In Mammalian Motoneuronsmentioning
confidence: 99%